ORTHODONTICS AND ITS IMPACT ON SLEEP QUALITY CAUSED BY OBSTRUCTIVE APNEA - Apolo Carrión, Yanderin Nicole; Rodríguez Robles, Carla Jessenia; Sauca Chalán, Nancy Pilar; Ordóñez Nieto, Mateo Eduardo; Yunga Picón, Maria Yolanda; Dávila Arcentales, Mónica Beatriz; Lafebre Carrasco, Milton Fabricio (RECISATEC - REVISTA CIENTÍFICA SAÚDE E TECNOLOGIA - ISSN 2763-8405, 2024)
Obstructive sleep apnea (OSA) is a respiratory disorder characterized by episodes of partial and/or complete obstruction during sleep, where breathing is interrupted or becomes shallow, resulting in decreased oxygen in the blood and micro-arousals that fragment sleep. The objective is to understand the connection between orthodontic or orthopedic treatments and the improvement they produce in this disorder. Identify the causes and consequences of obstructive sleep apnea in patients, as well as the effects of orthodontic treatments used to improve the condition. The search was conducted in PubMed, Scielo, Google Scholar, and Springerlink; MeSH terms "Sleep Apnea, Obstructive/therapy" AND Orthodontics.